The haze problem in Southeast Asia : palm oil and patronage - Varkkey, Helena (Abingdon, Oxon ; New York : Routledge, 2016)
'Despite the efforts of Southeast Asian governments and of ASEAN, transboundary haze continues to be a major environmental problem in Southeast Asia. This book demonstrates that the issue is complex, and explains why efforts to solve the problem in purely political terms are ineffective, and likely to continue to be ineffective'--
The Indonesian oil palm sector and haze -- The state as facilitator of regionalization -- Regionalization and patronage politics -- The regionalism of haze mitigation at the ASEAN level.
Includes bibliographical references and index.
Keywords: Air -- Pollution -- Political aspects -- Southeast Asia; Haze -- Environmental aspects -- Southeast Asia; Environmental protection -- Political aspects -- Southeast Asia